Pillararene‐Based Two‐Component Thixotropic Supramolecular Organogels: Complementarity and Multivalency as Prominent Motifs. Issue 59 (16th July 2018) - Zafrani, Yossi; Kaizerman, Dana; Hadar, Maya; Bigan, Nitzan; Granot, Eran; Ghosh, Moumita; Adler‐Abramovich, Lihi; Patolsky, Fernando; Cohen, Yoram
Abstract: Rationally designed two‐component supramolecular organogels based on multiple chemical interactions between percarboxylato‐ and peramino‐pillararenes are described. Mixing low concentration solutions (<1 % w/v) of decacarboxylato‐pillar[5]arene (1 ) with decaamino‐pillar[5]arenes (2 b –d ) affords, rapidly and without heating, organogels displaying an exceptional combination of properties. These supramolecular organogels, the characteristics of which are tunable, were found to be thixotropic and thermally stable, with T gel values in some cases exceeding the boiling point of the embedded solvent. It is demonstrated that both structural complementarity and multivalency are important determinants in the gelation process of these attractive soft materials. Abstract : Talkin′ ′bout my gelation : A rational design of a new family of supramolecular organogels based on percarboxylato‐ and perdialkylamino‐pillararenes is presented. These low minimal gelation concentration organogels—obtained with no heating—are thixotropic and thermally stable, with T gel in cases exceeding the boiling point of the solvent. Structural complementarity and multivalency are shown to be key determinants of their gelation process.